Europäische Volkswirtschaften im Lichte der Kreislauftheorie der Einkommensverteilung - Friedrich L. Sell; Michael Öllinger (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2017)
– In this paper, we present a combination of Keynesian and Kaldorian macroeconomic distribution theory. An important outcome of our research is that the (total) savings ratio is a positive function of the profit quota. In the empirical section of the paper, we first present the development of the saving quotas, of the profit quotas and of the total tax quotas among 8 European countries between 1999 and 2014. Furthermore, we conduct a linear regression analysis for the countries mentioned and find empirical support for a savings function in the vein of Nicholas Kaldor. We also find empirical support for the (modified) so-called second Keynesian equation. Finally, some economic policy thoughts and a summary with a scope for future research close our exposition.
Keywords: D30; D33; D63; 330; Keynesian and Kaldorian Approaches to Income Distribution; Income Distribution in European Economies; Empirical Estimates of Saving Functions